A Retrospective Evaluation of Serum Symmetric Dimethylarginine Concentration in Dogs With Protein‐Losing Enteropathy - Yeon Joon Park; Alexander J. German; David Brewer; Erin O'Connell (Journal of Veterinary Internal Medicine)
ABSTRACT Background Serum symmetric dimethylarginine (SDMA) is abnormally increased in people with inflammatory bowel disease (IBD). Changes in dogs with gastrointestinal disease, such as protein‐losing enteropathy (PLE), have not been assessed. Objectives Evaluate SDMA concentration in non‐azotemic dogs with PLE. Animals A total of 127 client‐owned dogs, 17 with PLE, 34 controls matched for age, breed, sex, and neuter status, and 76 additional controls for multiple linear regression modeling. Methods Retrospective case–control study. The clinical records of a United Kingdom referral hospital were reviewed. Dogs with azotemia or prior glucocorticoid or immunosuppressive treatment were excluded. Dogs diagnosed with PLE that had serum symmetric dimethylarginine (SDMA) concentrations measured were compared with the matched controls. Signalment, clinical presentation, clinicopathological abnormalities, treatment, and SDMA concentration pre‐ (PLE‐T0) and post‐ (PLE‐T1) treatment were recorded. Results At baseline, SDMA concentration was higher in PLE (T0, 15.2 ± 2.02 μg/dL) than in control (11.0 ± 3.13 μg/dL) dogs (p < 0.001; Hedge's G, 1.48), but decreased with treatment (PLE‐T1: 10.3 ± 2.78 μg/dL; T0 vs. T1: p = 0.01, Hedge's G, 1.31). Serum creatinine concentration was similar in PLE (T0, 0.81 ± 0.24 μg/dL) and control (0.85 ± 0.26 μg/dL) dogs at baseline (p = 0.57; Hedge's G, 0.18). Serum albumin concentration was lower in PLE (1.60 ± 0.51 g/dL) than in control (2.96 ± 0.49 g/dL) dogs (p < 0.001; Hedge's G, 2.68) before treatment, but increased with treatment (PLE‐T1: 2.29 ± 0.65 g/dL; T0 vs. T1: p = 0.003; Hedge's G, 1.14), although it remained lower than the concentration in controls (p = 0.002; Hedge's G, 1.23). No other clinicopathological differences were evident. Conclusions and Clinical Importance Serum SDMA concentration is increased in dogs with PLE; the clinical relevance of this finding requires further investigation.